"It was another skin": the kitchen in 1950s Western Australia - Supski, Sian (Curtin University, 2003)
This thesis examines the meanings of the kitchen to women who were wives, mothers, housewives and homemakers in the 1950s in Western Australia. It uses qualitative data collected from oral history interviews with migrant and Australian born women. Importantly, this thesis provides insight to women's everyday lives and analyses practices, such as cooking, ironing, budgeting, shopping, dishwashing and decorating which provide the women of my study with power. Central themes of this thesis include, examining the meaning of home and kitchen design, including discourses of efficiency and scientific management, decoration and consumption of appliances; analysing how practices of the kitchen inform women's multiple subjectivities; and the articulation and exercise of power throughout these practices.This research examines dualistic knowledge which has devalued women's position in the kitchen. Such dualistic knowledge is the basis of Western philosophy and informs not only patriarchal discourses of domesticity, femininity and efficiency, but also dominant architectural and design theory. Feminist poststructuralist theory, standpoint theory and feminist architectural theory provide a means of exploring women's knowledge and space of the kitchen. Such theories break down binaries and emphasise differences in/between women and explicate their practices (including the use of space) which encourage multiple identities. The kitchen is explored to show how dominant discourses reinforce gendered notions of women's work in the kitchen; also how women actively engage with architecture and design shaping it to suit their social relations and work processes within the kitchen; and the architecture and design of the kitchen is analysed as a means of examining women's input to design and decoration. Importantly, the thesis examines points of resistance - where women perform their practices, design their kitchens and decorate them in ways that perhaps were not intended by the dominant discourses.Thus, the thesis argues that women actively re/negotiate their embodied practices they disrupt, subvert and conform to patriarchal discourses of the kitchen in order to articulate a valued position within the kitchen.